Prophylactic use of nasalferon against COVID-19 in healthcare workers. Early surveillance study - Julio César Hernández Perera; Natalia Planas Sliuntiaeva; Susana Portela Collazo; Yadira Elvira Peña Guerra; Anselmo Antonio Abdo Cuza; Roberto Castellanos Gutiérrez; Mayka Caridad Guerrero Cancio; Dania Piñeiro Pérez; Ángela Tuero Iglesias (Universidad de Ciencias Médicas de La Habana, 2022)
Introduction: In Cuba, the nasal application of recombinant human IFN-alpha- 2b (nasalferon) began in personnel at risk in order to prevent SARS-CoV-2 infection. Objective: To characterize the safety in those subjects exposed to the use of Nasalferon at the Surgical Medical Research Center and to explore the effect of the prophylactic use of the drug against acute respiratory symptoms mainly caused by SARS-CoV-2. Material and Methods: Monocentric, prospective, open, and early surveillance epidemiological study conducted in healthcare workers who were administered Nasalferon. Surveillance was performed using the Prescription-Related Adverse Event Monitoring Surveillance method. The main variable was the presence of adverse events. Secondarily, the effect of the drug in preventing virus infection was explored. For the analysis of the main variable, the proportion of subjects who experienced each of the adverse events was estimated. In addition, the frequency distribution of the type of event, intensity, severity, and causality or imputability were estimated. Results: A total of 86 subjects were included; 50 of them experienced 15 types of adverse events. No severe or serious events were reported. Headache, leukopenia, decay, and arterial hypertension were classified as moderate ones. During the whole duration of the treatment and until a month after it, none of the subjects included in the study presented COVID-19 or other viral acute respiratory symptoms. Conclusions: Nasalferon proved to be a safe and tolerable drug and the included subjects did not present acute respiratory symptoms related or unrelated to COVID-19.